Pengaruh Model TPS Terhadap Kemampuan Berbicara Siswa Materi Teks Tanggapan Kelas IX SMP Negeri 2 Percut Sei Tuan - Rezki Antonio F. Ginting (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This study was motivated by the following problems, students' speaking ability is still low, students' confidence to speak in front of the class is still low, lack of vocabulary mastery in students. The sample was taken randomly, namely class IX-2 totaling 30 students as the experimental class and class IX-1 totaling 30 students as the control class. The method used was experimental method. The instrument used was a test. Hypothesis testing was done using the “t” test. The results showed that using the TPS model can improve students' speaking ability. This is evident from the average value obtained by students, namely 13% in the very good category, 60% in the good category, 27% in the sufficient category, 0% in the poor category, and 0% in the very poor category